La lectio divina en el Sínodo sobre la Palabra de Dios (segunda parte) - Izquierdo LC, Antonio (Alpha Omega, 2010)
One of the themes treated bay de Synod of the Bishops about the Word of God was the lectio divina. The author analyses, in this first part of his contribution, the various texts in what the lectio divina is mentioned in some interventions during the pre-synodal period and in the Relations and speeches of Synodal Fathers during the synodal phase.